2024
DOI: 10.1038/s41467-023-44547-7
|View full text |Cite
|
Sign up to set email alerts
|

Controllable strain-driven topological phase transition and dominant surface-state transport in HfTe5

Jinyu Liu,
Yinong Zhou,
Sebastian Yepez Rodriguez
et al.

Abstract: The fine-tuning of topologically protected states in quantum materials holds great promise for novel electronic devices. However, there are limited methods that allow for the controlled and efficient modulation of the crystal lattice while simultaneously monitoring the changes in the electronic structure within a single sample. Here, we apply significant and controllable strain to high-quality HfTe5 samples and perform electrical transport measurements to reveal the topological phase transition from a weak top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Due to the sensitivity of the transition metal pentatellurides’ electronic structure to lattice strain, our findings have important consequences for electronic transport measurements on such contacted and exfoliated films. Several studies provided evidence, including photoemission spectroscopy and electron transport, that the fundamental gaps of HfTe 5 , and similarly ZrTe 5 , can be strain-tuned across a weak to a strong topological insulator phase. ,,, Moreover, the location of additional, trivial carrier pockets depends on strain as well. , Therefore, our results may explain partly the considerable variation of results seen in the literature. While some studies reported a quasi-quantized Hall resistance of gapped Dirac Fermions with well-developed Shubnikov-de-Haas oscillations, , other studies reported signatures of anomalous Hall effects with largely suppressed Shubnikov-de-Haas oscillations, ,, sometimes even in nominally identical materials, and further studies described the transport features taking into account additional carrier pockets. Based on the substantial inhomogeneity of exfoliated films observed here, it may be advantageous to carefully and systematically differentiate between measurements on bulk crystal (mm-scale) and exfoliated films (μm-scale).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Due to the sensitivity of the transition metal pentatellurides’ electronic structure to lattice strain, our findings have important consequences for electronic transport measurements on such contacted and exfoliated films. Several studies provided evidence, including photoemission spectroscopy and electron transport, that the fundamental gaps of HfTe 5 , and similarly ZrTe 5 , can be strain-tuned across a weak to a strong topological insulator phase. ,,, Moreover, the location of additional, trivial carrier pockets depends on strain as well. , Therefore, our results may explain partly the considerable variation of results seen in the literature. While some studies reported a quasi-quantized Hall resistance of gapped Dirac Fermions with well-developed Shubnikov-de-Haas oscillations, , other studies reported signatures of anomalous Hall effects with largely suppressed Shubnikov-de-Haas oscillations, ,, sometimes even in nominally identical materials, and further studies described the transport features taking into account additional carrier pockets. Based on the substantial inhomogeneity of exfoliated films observed here, it may be advantageous to carefully and systematically differentiate between measurements on bulk crystal (mm-scale) and exfoliated films (μm-scale).…”
Section: Discussionmentioning
confidence: 55%
“…On the one hand, our results imply that inhomogeneities within the films have important implications for the interpretation of sometimes seemingly disparate results on microscale contacted films. On the other hand, we argue that Raman microscopy can be a valuable tool to pre- or postselect films with optimized homogeneity for further advanced experiments, e.g., on the topological properties of the materials and their circuits. , …”
mentioning
confidence: 97%
See 3 more Smart Citations